Enhancing the Quality of Life for Santri: Management of Pesantren through the Strengthening of Clean and Healthy Living Culture - Gafur, Abdul; Zainuddin, Muhammad; Walid, Muhammad; Barizi, Ahmad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to analyze Islamic boarding school management based on strengthening a clean and healthy living culture to improve student's quality of life. This research uses a qualitative approach with a case study design. Data collection was carried out through observations, interviews and document analysis. Data analysis includes data collection activities, reduction, presentation, and conclusion. Credibility, transferability, dependability and confirmability tests are used to check the data's validity. The results of this research conclude that Islamic boarding school management based on strengthening a culture of clean and healthy living is carried out through systemic stages and processes so that it can improve the quality of life of students and the image of the institution while breaking negative assumptions that are often associated with Islamic boarding school life as a shabby and dirty institution and able to change people's views and perceptions about Islamic boarding schools in a more positive direction. This research implies that Islamic boarding school management based on a culture of clean and healthy living not only improves students' quality of life but also the institution's image as a whole.